Avaliação da degradação biótica do poli(ácido lático), do polipropileno e suas misturas pela ação de fungos basidiomicetos - Menegotto, Morgana (My University, 2015)
Polymeric wastes when intended improperly, associated with its resistance to degradation may promote environmental pollution. Therefore, studies involving the degradation of some polymers are considered as an alternative to current environmental pollution problems. Another alternative that allows changing the characteristics of interest of the polymers is through the development of polyblends, and their physical and chemical properties can be changed to a wide range of applications, providing desirable performance to the final product. In this work were used polypropylene (PP), synthetic polymer, and polylactic acid (PLA), biodegradable polymer with and without the presence of compatibilizer (AC) based maleic anhydride modified PP. The objective of this study was to evaluate the properties of the blend of PLA and PP with and without the presence of compatibilizer as well the action of 10 basidiomycete fungi isolated from biomes, rainforest and pampa in as individually degradation polymers and the blends of PLA/PP. Polyblends of PP and PLA with and without the presence of a compatibilizer were produced by extrusion and injection process and morphological analysis, thermal, chemical and mechanical properties. For the process of biological degradation in solid culture in vitro were produced films of PP, PLA and their blend by compression molding. The pure polymers were subjected to exposure to the ten basidiomycete fungi for a period of 14, 28 and 75 days at 28°C, being the fungi Trametes villosa (Sw.) Kreisel 82I.6, Schizophyllum cf. commune (Fr.) 85E.16 and Auricularia bull Ex. Juss. 551.9B those who have provided evidence of degradation in the films of PLA and the fungus T. villosa (Sw.) Kreisel 82I.6 in the films of PP. A blend of PLA/AC/PP 75/3/25 selected due to its higher hydrophilic character, was subjected to exposure to the fungus T. villosa (Sw.) Kreisel 82I.6 during 14, 28 and 60 days at 28°C. After the evaluation period the physical properties (weight loss), morphological (light microscopy and scanning lectron microscopy) and chemical characteristics (infrared spectroscopy with Fourier transform) were observed. As a result of the properties of the blends, these proved to be immiscible, and the mechanical properties were lower than those of the PLA, without change in thermal stability and change in hydrophilicity with PP increasing. PLA decreased crystallinity after processing and PP increased. The solutions produced in liquid culture of the PLA with fungi T. villosa (Sw.) Kreisel 82I.6, S. cf. commune (Fr.) 85E.16 and A. bull Ex Juss. 551.9B and PP with the fungus T. villosa (Sw.) Kreisel 82I.6, however, the enzymes were not as efficient biological degradation in the broth. The fungi that showed higher degradation potential in solid culture of PLA were the T. villosa (Sw.) Kreisel 82I.6, S. cf. commune (Fr.) 85E.16 and A. bull Ex. Juss 551.9B below those reported in the literature time and the PP, the fungus T. villosa (Sw.) Kreisel 82I.6.; it promoted surface changes with removal of material after 28 and 75 days of incubation. The fungus T. villosa (Sw.) Kreisel 82I.6 used in the process of degradation in solid culture blend PLA/AC/PP (75/3/25), was identified that provided evidence of degradation during periods of exposure this study.
Resíduos poliméricos, quando destinados em ambientes inadequados, associados a sua resistência à degradação, podem promover poluição ambiental. Desta forma, estudos que possibilitam favorecer a degradação de alguns polímeros vêm crescendo e são considerados como alternativa para os atuais problemas de poluição ambiental. Outra alternativa que possibilita alterar características de interesse dos polímeros é por meio do desenvolvimento de misturas poliméricas, sendo que suas propriedades físicas e químicas podem ser alteradas para uma vasta gama de aplicações, proporcionando desempenho desejável ao produto final. Neste trabalho foi desenvolvida misturas poliméricas entre o polipropileno (PP), polímero sintético, e o poli(ácido lático) (PLA), polímero biodegradável com e sem a presença de agente compatibilizante (AC) a base de PP modificado com anidrido maleico. O objetivo do trabalho foi avaliar as propriedades da mistura de PLA e PP sem e com a presença de agente compatibilizante, bem como a ação de 10 fungos asidiomicetos isolados dos biomas mata atlântica e pampa na degradação individualmente dos polímeros e da mistura de PLA/PP. As misturas poliméricas foram produzidas por processo de extrusão e injeção e verificadas as propriedades morfológicas, térmicas, químicas e mecânicas. Para o processo de degradação biológica em cultivo sólido in vitro foram produzidos filmes de PP, PLA e suas misturas, por moldagem por compressão. Os polímeros puros foram submetidos à exposição aos 10 fungos por períodos de 14, 28 e 75 dias a 28°C sendo os fungos Trametes villosa (Sw.) Kreisel 82I.6, Schizophyllum cf. commune (Fr.) 85E.16 e Auricularia bull Ex. Juss. 551.9B os que proporcionaram indícios de degradação nos filmes de PLA e o fungo T. villosa (Sw.) Kreisel 82I.6 nos filmes de PP. A mistura de PLA/AC/PP (75/3/25) selecionada por apresentar maior caráter hidrofílico, foi submetida à exposição ao fungo T. villosa (Sw.) Kreisel 82I.6 por 14, 28 e 60 dias a 28°C. Após o período avaliado, foram verificadas as propriedades físicas (perda de massa), morfológicas (microscopia ótica e microscopia eletrônica de varredura) e características químicas (espectroscopia no infravermelho com transformada de Fourier). Como resultados das propriedades das misturas, estas mostraram-se imiscíveis e as propriedades mecânicas foram inferiores as do PLA, sem alteração da estabilidade térmica e mudança da hidrofilia com o aumento de PP. O PLA diminuiu sua cristalinidade após o processamento e o PP aumentou. Foram produzidos extratos em cultivo líquido do PLA com os fungos T. villosa (Sw.) Kreisel 82I.6, S. cf. commune (Fr.) 85E.16 e A. bull Ex. Juss. 551.9B e do PP com o fungo T. villosa (Sw.) Kreisel 82I.6, contudo as enzimas não foram eficientes quanto a degradação biológica nos caldos. Os fungos que apresentaram maior potencial de degradação em cultivo sólido do PLA foram o T. villosa (Sw.) Kreisel 82I.6, S. cf. commune (Fr.) 85E.16 e A. bull Ex. Juss 551.9B e para o PP foi o fungo T. villosa (Sw.) Kreisel 82I.6; evidenciado na colonização da superfície com remoção de material após 28 e 75 dias de incubação. O fungo T. villosa (Sw.) Kreisel 82I.6 utilizado no processo de degradação em cultivo sólido da mistura PLA/AC/PP (75/3/25) propiciou que fosse identificado indícios de degradação nos períodos estudados.
Keywords: Polímeros - Deterioração; Basidiomicetos; Química analítica qualitativa; Poluição; Polymers - Deterioration; Basidiomycetes; Chemistry, Analytic qualitative; Pollution